Cancer recurrence and mortality after pediatric heart transplantation for anthracycline cardiomyopathy: A report from the Pediatric Heart Transplant Study (PHTS) group. (4th April 2017) - Bock, Matthew J.; Pahl, Elfriede; Rusconi, Paolo G.; Boyle, Gerard J.; Parent, John J.; Twist, Clare J.; Kirklin, James K.; Pruitt, Elizabeth; Bernstein, Daniel
Abstract: We aimed to determine whether malignancy after pediatric HTx for ACM affects overall post‐HTx survival. Patients <18y listed for HTx for ACM in the PHTS database between 1993 and 2014 were compared to those with DCM. A 2:1 matched DCM cohort was also compared. Wait‐list and post‐HTx survival, along with freedom from common HTx complications, were compared. Eighty subjects were listed due to ACM, whereas 1985 were listed for DCM. Although wait‐list survival was higher in the ACM group, post‐HTx survival was lower for the ACM cohort. Neither difference persisted in the matched cohort analysis. Primary cause of death in the ACM group was infection, which was higher than the DCM group. Malignancy rates were not different. All ACM malignancies were due to PTLD without primary cancer recurrence or SMN. Long‐term graft survival after pediatric HTx for ACM is no different than for matched DCM peers, nor is there an increased risk of any malignancy. However, risk of infection and death from infection after HTx are higher in the ACM group. Further studies are needed to assess the effects of prior chemotherapy on susceptibility to infection in this group.